Preserved Function of Afferent Parvalbumin-Positive Perisomatic Inhibitory Synapses of Dentate Granule Cells in Rapidly Kindled Mice - Hansen, Marita G.; Ledri, Litsa N.; Kirik, Deniz; Kokaia, Merab; Ledri, Marco (Frontiers in Cellular Neuroscience, 2018)
Parvalbumin- (PV-) containing basket cells constitute perisomatic GABAergic inhibitory interneurons innervating principal cells at perisomatic area, a strategic location that allows them to efficiently control the output and synchronize oscillatory activity at gamma frequency (30–90 Hz) oscillations. This oscillatory activity can convert into higher frequency epileptiform activity, and therefore could play an important role in the generation of seizures. However, the role of endogenous modulators of seizure activity, such as Neuropeptide Y (NPY), has not been fully explored in at PV input and output synapses. Here, using selective optogenetic activation of PV cells in the hippocampus, we show that seizures, induced by rapid kindling (RK) stimulations, enhance gamma-aminobutyric acid (GABA) release from PV cells onto dentate gyrus (DG) granule cells (GC). However, PV-GC synapses did not differ between controls and kindled animals in terms of GABA release probability, short-term plasticity and sensitivity to NPY. Kinetics of gamma-aminobutyric acid A (GABA-A) mediated currents in postsynaptic GC were also unaffected. When challenged by repetitive high-frequency optogenetic stimulations, PV synapses in kindled animals responded with enhanced GABA release onto GC. These results unveil a mechanism that might possibly contribute to the generation of abnormal synchrony and maintenance of epileptic seizures.